Assembling Health Care Organizations Practice, Materiality and Institutions - Lindberg, Kajsa. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
Assembling Health Care Organizations combines an institutional theory perspective with a materialist view of the technologies, devices, biological specimens, and other material resources mobilized and put to work in health care work.